Long-term outcome of multiform premature ventricular complexes in structurally normal heart. (1st February 2015) - Lin, Chin-Yu; Chang, Shih-Lin; Lin, Yenn-Jiang; Lo, Li-Wei; Chung, Fa-Po; Chen, Yun-Yu; Chao, Tze-Fan; Hu, Yu-Feng; Tuan, Ta-Chuan; Liao, Jo-Nan; Huang, Yen-Chang; Chang, Yaoting; et al.
Abstract: Background: Multiform premature ventricular complexes (PVCs) are common electrocardiographic abnormalities in patients with structurally normal hearts. However, the prognostic value of these complexes remains unclear. This study aimed to clarify the role of PVC polymorphism in predicting adverse outcomes. Methods and result: We examined the database for 24-hour electrocardiography monitoring between January 1, 2002 and December 31, 2004. We analyzed 3351 individuals with apparently normal hearts. Kaplan–Meier curves and multivariate Cox proportional hazards models were employed to estimate the effect of multiform PVC and uniform PVC on the number of incident adverse events. Average follow-up time was 10 ± 1 years. Patients with multiform PVC were older and had a higher prevalence of comorbidities. In multivariate analysis, patients with multiform PVC had an increased incidence of mortality (hazard ratio [HR]: 1.642, 95% confidence interval [CI]: 1.327–2.031), hospitalization (HR: 1.196, 95% CI: 1.059–1.350), cardiovascular hospitalization (HR: 1.289, 95% CI: 1.030–1.613), new-onset heart failure (HF; HR: 1.456, 95% CI: 1.062–1.997), transient ischemic accident (HR: 1.411, 95% CI 1.063–1.873), and new-onset atrial fibrillation (AF; HR: 1.546, 95% CI: 1.058–2.258) compared to the group without PVC. Patients with multiform PVC had a higher rate of mortality (HR: 1.231, 95% CI: 1.033–1.468) and all cause-hospitalization (HR: 1.147, 95% CI: 1.025–1.283) compared with patients with uniform PVC. Conclusion: The presence of multiform PVC was associated with a higher incidence of mortality, hospitalization, transient ischemic attack, new-onset AF, and new-onset HF independent of other clinical risk factors. Highlights: Presence of multiform PVC in 24-hours Holter monitoring was associated with a higher risk of mortality independent of the clinical risk factors in patients with apparently normal hearts. Presence of multiform PVC in 24-hours Holter monitoring was associated with a higher risk all-cause hospitalization and CV hospitalization independent of the clinical risk factors in patients with apparently normal hearts. Presence of multiform PVC in 24-hours Holter monitoring was associated with a higher risk of TIA, new-onset AF, and new-onset HF independent of the clinical risk factors in patients with apparently normal hearts.